Assessing changes in the UK pet cat and dog populations: numbers and household ownership. (12th September 2015) - Murray, J. K.; Gruffydd‐Jones, T. J.; Roberts, M. A.; Browne, W. J.
Abstract : The main aim of this study was to replicate methodology used to estimate the size of the UK pet cat and dog populations in 2006 and the proportion of households owning cats/dogs in 2007, to produce updated data to compare trends in ownership and population sizes. A cross‐sectional study design was used to collect telephone interview data from 3155 households in the UK. 2011 UK human census data were used to predict the size of the cat and dog populations owned by households in the UK in 2011. Of the households, 23 per cent (714/3155) owned one or more cats and 30 per cent (940/3155) owned one or more dogs. There was some overlap in pet ownership with 7 per cent (210/3155) of households owning both one or more cats and one or more dogs. There was a small but significant decrease in the proportion of households that owned one or more cats in 2011 compared with 2007, with no change in the proportion owning dogs. However, overall, the total number of cats and dogs that were estimated to be owned by UK households did not change significantly between 2006 and 2011. The estimated size (and 95% CIs) of the pet cat and dog populations in the UK in 2011 was 10, 114, 764 cats (9, 138, 603–11, 090, 924) and 11, 599, 824 dogs (10, 708, 070–12, 491, 578).